2018
DOI: 10.3389/fimmu.2018.01905
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus sakei WIKIM30 Ameliorates Atopic Dermatitis-Like Skin Lesions by Inducing Regulatory T Cells and Altering Gut Microbiota Structure in Mice

Abstract: Lactobacillus sakei WIKIM30 is a Gram-positive facultative anaerobic bacterium isolated from kimchi, a Korean fermented vegetable food. In this study, we found that WIKIM30 promoted regulatory T cell (Treg) differentiation by inducing dendritic cells with tolerogenic properties. The production of the T helper (Th) 2-associated cytokine interleukin (IL)-4 was decreased, but that of the Treg-associated cytokine IL-10 was increased in splenocytes from ovalbumin-sensitized mice treated with WIKIM30. We also invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 49 publications
4
63
0
4
Order By: Relevance
“…In the future, to confirm these mechanistic differences, it will be necessary to test the immune status of mice treated with the FP strain prior to OVA sensitization. Kwon et al reported that oral administration of L. sakei WIKIM30 induces tolerogenic DCs and Treg cells, thereby improving allergic symptoms in mouse models of allergic dermatitis (48). It also has been reported that oral administration of Bifidobacterium increases Treg numbers and improves allergic symptoms in OVA-sensitized allergy model mice (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…In the future, to confirm these mechanistic differences, it will be necessary to test the immune status of mice treated with the FP strain prior to OVA sensitization. Kwon et al reported that oral administration of L. sakei WIKIM30 induces tolerogenic DCs and Treg cells, thereby improving allergic symptoms in mouse models of allergic dermatitis (48). It also has been reported that oral administration of Bifidobacterium increases Treg numbers and improves allergic symptoms in OVA-sensitized allergy model mice (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus sakei WIKIM30 proved to ameliorate atopic dermatitis skin lesions by T reg -cell induction and altering intestinal microbiota in mice, Lactobacillus casei variety rhamnosus alleviated mice model of induced atopic dermatitis by increasing Bifidobacterium, Lactobacilli, Enterococcus and Bacteroides fragilis levels and decreasing Clostridium coccoides amounts and attenuative effects on skin inflammation in mice was also observed in case of Lactobacillus salivarius LA307 and Lactobacillus rhamnosus LA305. [112][113][114][115] Furthermore, probiotics have shown to present antipruritic effects in AD. 116,117 The meta-analysis carried out by Chang et al 118 supported synbiotics in the AD therapy, especially among 1-year old and older children.…”
Section: Hidradenitis Suppurativamentioning
confidence: 99%
“…Colonization of the gut with Bifidobacterium , Lactobacillus , and some Clostridium spp. in germ‐free mice was found to be associated with Treg cell proliferation . Conversely, gut dysbiosis, involving a reduction in the abundance of these microorganisms, may lead to a reduction in the number of Treg cells or impaired function, which in turn affects the development of immune tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…in germ-free mice was found to be associated with Treg cell proliferation. 26,27 Conversely, gut dysbiosis, involving a reduction in the abundance of these microorganisms, may lead to a reduction in the number of Treg cells or impaired function, which in turn affects the development of immune tolerance. Given that GDM is associated with a high risk of allergic disease in the offspring, 11 we hypothesized that dysbiosis of the gut microbiome of the offspring of GDM mothers might contribute to the disruption of normal immune balance and impaired development of immune tolerance.…”
Section: Introductionmentioning
confidence: 99%